Third-Degree B-spline solution for a nonlinear diffusion Fisher’xxs equation - Çağlar, Hatice Nazan; Çağlar, Süleyman Hikmet; İşeri, Müge (My University, 2011)
Non-linear Fisher’s equations are solved by using a spline method based on B-spline in the space direction and finite difference schema in the time direction. Numerical results reveal that spline method based on Bspline is implemented and effective
Keywords: Non-linear Fisher’s equations; Finite difference; Bspline functions; Boundary conditions